2012
DOI: 10.5539/ijb.v4n2p3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Differences in Breast Cancer Patients Compared to Matched Controls Prior to Chemotherapy

Abstract: Understanding the relationship between chemotherapy and cognitive impairment requires information on pre-treatment variability between cancer patients and well-matched controls. The purpose of this study was to investigate neuroanatomical differences between breast cancer (BC) patients and controls, prior to chemotherapy,controllingfor possible confounding variables. Twenty-three female early-stage BC patients underwent MRI scanning after surgery but before chemotherapy and were sex-, age-and education-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 74 publications
3
33
0
Order By: Relevance
“…Structural [15, 19, 34] and functional MRI [23, 24, 35] studies have found that abnormalities may already exist in the absence of chemotherapy for breast cancer patients. More recent neuroimaging studies of other types of cancer including lung [26] and testicular cancer [27] also suggest that structural abnormalities exist without chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Structural [15, 19, 34] and functional MRI [23, 24, 35] studies have found that abnormalities may already exist in the absence of chemotherapy for breast cancer patients. More recent neuroimaging studies of other types of cancer including lung [26] and testicular cancer [27] also suggest that structural abnormalities exist without chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In one study semi-automatic segmentation procedure was used [34] and in three automatic seqmentation procedure were used [10, 13, 39]. Most of the studies were conducted in cross-sectional design: 10 in breast cancer survivors treated with CTx [4, 6, 10, 13, 34, 35, 3840, 43] and 2 in breast cancer patients prior to CTx [41, 58]; 5 studies were conducted with longitudinal design [11, 36, 37, 61, 62]. The results obtained from breast cancer patients treated with CTx were compared to breast cancer patient without CTx [34, 38, 55], healthy controls [4, 10, 13, 35, 40, 41, 62], non-cancer reference subjects [39, 43], or breast cancer patients without CTx and healthy controls [6, 36, 37, 58, 61].…”
Section: Structural Changes In the Central Nervous System Of Women Wimentioning
confidence: 99%
“…Most of the studies were conducted in cross-sectional design: 10 in breast cancer survivors treated with CTx [4, 6, 10, 13, 34, 35, 3840, 43] and 2 in breast cancer patients prior to CTx [41, 58]; 5 studies were conducted with longitudinal design [11, 36, 37, 61, 62]. The results obtained from breast cancer patients treated with CTx were compared to breast cancer patient without CTx [34, 38, 55], healthy controls [4, 10, 13, 35, 40, 41, 62], non-cancer reference subjects [39, 43], or breast cancer patients without CTx and healthy controls [6, 36, 37, 58, 61]. In four studies breast cancer patients were treated with the same schema of CTx [38, 39, 43, 58] and in the other studies different schemas were applied [4, 6, 1013, 3437, 40, 42].…”
Section: Structural Changes In the Central Nervous System Of Women Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Such variability makes it difficult to convince those outside the patient population of the reality of cognitive impairments found in cancer patients undergoing or having completed chemotherapy. The considerable variability in results from one study to the next are due to differences in key study design factors including: (1) sample size (many studies use only a small number of patients), (2) differences in the nature of the neuropsychological battery used (e.g., targeted tests or complete battery) resulting in differential sensitivity to subtle cognitive changes, (3) increased sensitivity of computerized testing in conjunction with pencil and paper assessments, (4) nature of the control group (example: healthy controls vs. non-chemotherapy patient group), (5) definition and/or criteria of cognitive impairment adopted, (6) effects of anesthesia on cognition for patients who also underwent surgery [27], (7) stress of cancer diagnosis and treatment, (8) existence of pre-treatment differences in cognition between BC patients and controls [2831], (9) possible negative effects of endocrine treatment on cognition [23], and (10) data analysis methods used, in particular, whether impairment is defined at the group or individual level and, in the case of longitudinal studies, whether or not the analyses control for practice effects associated with repeated testing. These factors must be systematically controlled in future studies if progress is to be made in understanding the effects of cancer treatments on cognition.…”
Section: Introductionmentioning
confidence: 99%